Access and utilization of youth friendly sexual and reproductive health services among illiterate adolescents in Rwanda: A mixed-methods participatory study - Madeleine Mukeshimana; Aimable Nkurunziza; Gerard Nyiringango; Eliphaz Karamage; Domina Asingizwe; Claudine Nshutiyukuri; Sandra Musabwasoni; Vedaste Bagweneza; Michael Habtu; Josephine Uzayisenga; Oluyinka Adejumo; Endale Tamrat (PLoS ONE, 2025)
Background Youth Friendly Health Services Centers (YFHS) in Rwanda have been established to address the lack of information and services related to reproductive health. However, there is a paucity of studies investigating the hurdles faced by illiterate adolescents when seeking sexual and reproductive health services. This study assessed adolescents’ sexual and reproductive health (ASRH) accessibility and utilization in YFHS among illiterate adolescents in Rwanda. Methods This study used a mixed-method participatory study design. One hundred fifty illiterate adolescents were recruited using a convenience sampling. A checklist was used to observe the 16 YFHS. In the quantitative phase, data were organized using Statistical Package for the Social Sciences (SPSS) version 26, and analyzed through descriptive and inferential statistics. Two focus group discussions moderated by trained illiterate adolescents were conducted. Data were organized using Dedoose software and analyzed thematically. Results The proportion of YFHS utilization was 25.3%. In the multivariate regression analysis, five outcomes remained significant to utilize YFHS: ever heard about YFHS (Adjusted Odds Ratio [AOR] = 6.32; 95% Confidence Interval [CI] = 2.07–19.27, having ASRH information (AOR = 8.99; 95 CI = 1.43–56.77), having information about any family planning (AOR = 19.00; 95 CI = 1.52–236.84), use of any type of contraceptives (AOR = 4.45; 95%CI = 1.34–14.85), and having information on prevention and management (AOR = 24.99; 95 CI = 2.76–226.53). Observers rated the quality of SRHs in YFHS at 24.36%. Facilitators to access YFHS include having information about ASRH, free-of-charge services, and peer educators. The reported barriers included providers’ negative attitudes, internalized stigma, and lack of materials tailored to illiterate adolescents. The study participants suggested ways to improve the YFHS, such as community awareness, staff training, entertainment, and increasing the number of YFHS. Conclusions The utilization of YFHS among illiterate adolescents remains low, highlighting the need for targeted interventions to improve access and quality. Key facilitators, such as access to information, peer education, and free services, should be strengthened, while addressing barriers like provider attitudes, stigma, and resource limitations. These findings underscore the necessity of enhancing both the accessibility and quality of YFHS to ensure comprehensive reproductive health care for illiterate adolescents.